The relationship between mental stress and hypertensive disorders during pregnancy: A review article - Nayereh Aazam Haji Khani; Giti Ozgoli; Taghi Pour Ebrahim; Zeinab Hamzeh Gardeshi (Mashhad University of Medical Sciences, 2017)
Introduction: The results of the studies are different about the relationship between mental stress and hypertensive disorders as one of the most important unresolved issues in obstetrics. This review study was performed with aim to present a regulated collection of recent studies on the relationship between mental stress and hypertensive disorders during pregnancy. Methods: In this review study, the related English and Persian papers were collected from databases of Google scholar, Pubmed , Scienc direct , SID , Irandoc and using the key words of stress, mental, preeclampsia and the Persian words of stress, preeclampsia, eclampsia, pregnancy- induced hypertension, and toxemia from 1980 to 2017. The papers which got the score of 16 in evaluation based on STROBE checklist were entered to this study. Results were presented as qualitative report. Results: Finally, 8 papers were entered to the study that evaluated different type of stress by various scales. In these studies, there was no sufficient homogeneous for combining data, so data were only reported. Among these studies, there was significant relationship between maternal mental stress and hypertensive disorders in 6 studies and no relationship was found in other two studies. Conclusion: In majority of studies, there was relationship between stress and hypertensive disorders. However, more prospective analytical studies with controlling confounding variables is required to more determine this relationship.